Prediksi Persediaan Material Menggunakan Metode Single Exponential Smoothing - noeman noeman; Fadhila Fajri Putri; Rakhmat Purnomo; Robertus Suraji (Journal of Practical Computer Science, 2022)
Material is an important material in manufacturing companies that make components of an item. Used to make various components which are then processed on injection machines. This of course makes warehouse and Production Planing Inventory Control (PPIC) employees have to see and ensure that the availability of materials can be fulfilled for several days or months, then make planning for spending or using materials if the existing materials have reached the availability limit. , and also inconsistent data such as lack of material. The purpose of this study is to find out how much material inventory is for the next 1 period. The method used is Single Exponential Smoothing with a constant of 0.9. Provision of constants for calculations from the High Impact Polystyrene (HIPS) 495F NATURAL material data sample which is applied to 3 other types of materials. The result of this research is that for PBT DURANEX 3300 NATURAL, the result is 777.01 with MSE 2880745.72, MAD 489.96 and MAPE 0.074%. ABS material type TOYOLAC T500-322 NATURAL got 2813.18 results with MSE 342161.98, MAD 168.85, and MAPE 0.092%. Material Type AS STYLAC 769 6A-X8113 IVORY got 663.46 results with MSE 222210.16, MAD 136.07, and MAPE 0.092%.